MEMS piezoelectric micro power harvester physical parameter optimization, simulation, and fabrication for extremely low frequency and low vibration level applications. (October 2020) - Alrashdan, Mohd H.S.
Abstract: In the last decade, the Piezoelectric Micro Power Harvesters (PMPH) has had a significant attention to produce self-powered small electronic devices at high frequency range. This paper discusses the effects of the PMPH control factor on the PMPH performances including Electric Energy Density and the Normal Electric Field using Taguchi optimization method. Furthermore, the study uses the ANOVA test and the Multivariable linear Regression model to confirm the Taguchi method. Also, it studies the PMPH with optimal control factor simulate through COMSOL Multiphysics 5.4 software. Then, it studies the PMPH first resonance frequency mode with Eigen-Frequency analysis. Moreover, the PMPH performances simulate in time domain through the transient analysis. Therefore, the PMPH is fabricated; it uses silicon substrate coated on both sides with a silicon nitride insulation layer, piezoelectric material is deposited on top of the insulation layer using the RF sputtering technique, the interdigitated gold electrodes (IDEs) are deposited using the DC sputtering, and a proof mass is used to lower the resonance frequency. Furthermore, the fabricated PMPH will be tested with base shaker experiment. Taguchi, ANOVA, and multivariable linear regression analyses results confirm each other. The paper concludes that the piezoelectric material, piezoelectric layer thickness, and silicon membrane thickness are the most three-factors influence the PMPH performances at low vibration levels and extremely low frequency about 1.2 Hz. On the other hand, the piezoelectric layer width and insulator width are the lowest control factors affect the PMPH performances. The PMPH with an optimum parameters simulation results as following, it vibrates at 2.59 Hz with an acceleration magnitude of 0.9 g and the maximum electric energy density of 400 Jm −3 . The fabricated PMPH vibrates at the first resonance frequency of 1.2 Hz with acceleration magnitude of 0.9 g. Also, the study finds out that the optimum loading resister of 200 KΩ is found, associated with open-circuit voltage of 18.52 Vp−p . Also, the PMPH produces a maximum electric output power of 135  μ W and maximum electric power density of 26.1 mWCm −3 . The PMPH Simulation and fabrication results support each other and they demonstrate that the proposed PMPH can work probably at low vibration levels and at extremely low frequency about 1 Hz. Which makes the PMPH suitable for powering small electronic devices, such as cardiac pacemakers and other small medical implants.